Acute haemolytic anemia with liver failure as initial clinical manifestations of Wilson's Disease. - Komina, Selim; Petrushevska, Gordana; Spasevska, Liljana; Janevska, Vesna; Kostovski, Aco; Zdravkovski, Panche; Grujovska, S; Jankovska, B (Springer, 2015)
Objective: Wilson's disease is an autosomal recessive disorder of copper transport. It results in accumulation of copper in the liver, brain, and other organs. Severe hemolytic anemia is an unusual clinical presentation. Since effective treatment is available for this disease, early and correct diagnosis is important. We report a case of a previously undiagnosed Wilson's disease revealed by acute intravascular hemolytic anemia and liver failure as an initial manifestation of disease. Method: A previously healthy, 11-year-old boy, presenting with abdominal pain, jaundice, tea-colored urine, and anemia was admitted to the pediatric hospital. Clinical and laboratory investigations for suspected hematological and hepatic disorder were immediately taken. Blood sample for genetic testing for Wilson's disease was performed. The patient was treated with plasmapheresis and other supportive treatment, but unfortunately the condition turned fatal 6 days after hospitalization. Results: Autopsy revealed shock with hemolytic anemia and respiratory distress syndrome superimposed on liver cirrhosis. Positive Orcein-Shikata and Rubeanic acid stain, ultrastructural visualization of electron-dense lysosomal deposits and liver copper content analysis, in conjuction with genetic results, confirmed the diagnosis of Wilson's disease as cause of cirrhosis. Conclusion: Wilson's disease must be considered in case of acute hemolytic anemia associated with liver failure in young adults.
Keywords: Wilson; copper; hemolytic anemia; cirrhosis; liver